Effects of Pop Culture for Improving Student-Teachers’ Writing Skill (A Case Study at Galuh University) - Ratnawati, Ratnawati (Universitas Swadaya Gunung Jati, 2016)
Writing, one of the four skills which have to be taught by educators in language learning. Starting from classroom observation implied that students confronted the difficulties in writing involving generating ideas, organizing words, and making compositions. This study supposes to explore some effects of pop culture as authentic materials for English language teaching in improving students’ writing skill. Due to pop culture relates to students’ life and experience, it is considered to be a stimulus for gaining students’ ideas, information, motivation, and interest in teaching writing. The students of secondary school were involved in this study and descriptive case study was employed to observe the importance of pop culture in writing class. Also, questionnaires and students’ works are the instruments to measure its effects. Both students’ works and result of the questionnaires pointed out that significantly improvement obtained after applying pop culture. In line with findings, it can be said that pop cultures have significant effects toward students’ writing skill. So, educators need to apply pop culture as their choices in future planning lesson.